ANALISIS DAMPAK SCREEN TIME TERHADAP KONSENTRASI BELAJAR SISWA KELAS V SEKOLAH DASAR - Azzahra, Syahraz; Satibi Hidayat, Otib; Hasanah, Uswatun (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the impact of screen time on the learning concentration of fifth-grade students at SDN Jatiwaringin XIII. This study employs a qualitative approach using a descriptive case study design. Data were collected through observation, interviews, and documentation involving five students and the classroom teacher. The results indicate that screen time affects students’ learning concentration, particularly when used for extended periods dominated by entertainment activities. Students tend to experience a decline in focus and are easily distracted during learning. However, screen time can also have a positive impact when used to support learning. Therefore, supervision and control of gadget use by teachers and parents are necessary to ensure it does not disrupt students’ concentration during learning.